Synthesis of bioactive and fluorescent pyridine-triazole-coumarin peptidomimetics through sequential click-multicomponent reactions. Issue 3 (1st February 2017) - Soumya, T.V.; Muhammed Ajmal, C.; Bahulayan, D.
Graphical abstract: Highlights: Step economic synthesis for coumarin-triazole-pyridine peptidomimetics. Blue emitting molecules with low band gap. Belongs to extended rule of 5 (eRo5) chemical space. Intense fluorescence with large Stokes shift. Suitable for the development of fluorescent markers. Suitable for the development of drugs for undruggable targets. Abstract: An easy synthetic protocol for the peptide randomization of 3, 5-dicyano pyridine derivatives by linking the pyridine core with a coumarin chromophore spaced by a linker triazole via copper (I) catalyzed [3 + 2] azide-alkyne cycloaddition (CuAAC) is described. The new peptidomimetics thus obtained are extended rule of 5 (eRo5) molecules suitable for the development of therapeutic agents for undruggable targets. The structural and photophysical properties of the molecules are also promising for the development of potential bio imaging agents based on these molecules.